Large-scale quantification of CVD graphene surface coverage - Ambrosi, Adriano (2013)
The extraordinary properties demonstrated for graphene and graphene-related materials can be fully exploited when a large-scale fabrication procedure is made available. Chemical vapor deposition (CVD) of graphene on Cu and Ni substrates is one of the most promising procedures to synthesize large-area and good quality graphene ﬁlms. Parallel to the fabrication process, a large-scale quality monitoring technique is equally crucial. We demonstrate here a rapid and simple methodology that is able to probe the eﬀectiveness of the growth process over a large substrate area for both Ni and Cu substrates. This method is based on inherent electrochemical signals generated by the underlying metal catalysts when fractures or discontinuities of the graphene ﬁlm are present. The method can be applied immediately after the CVD growth process without the need for any graphene transfer step and represents a powerful quality monitoring technique for the assessment of large-scale fabrication of graphene by the CVD process.